The Fisher model and financial markets - MacMinn, Richard D. (World Scientific Pub., 2005)
This monograph represents a unified coherent perspective of financial markets and the theory of corporate finance. The Fisher model is used in corporate finance texts to note the foundations of the net present value rule, but has not been developed further in textbooks as a perspective for students of the finance discipline. This book articulates corporate finance from a common perspective and model: by generalizing the Fisher model to include risks, it is possible to exposit and prove the classic corporate finance theorems and to establish a common foundation for the discipline. The classic t.